Efecto del método de hidrólisis y temperatura de deshidratación en la calidad bromatológica, fisicoquímica y rendimiento de colágeno de patas de pollo - Ormaza Mendieta, Selene Stefania (2024)
The objective of this research was to determine the effect of the hydrolysis method and dehydration temperature on the bromatological and physicochemical quality and yield of chicken leg collagen. An experimental method was applied where two factors with two levels were studied, evaluating the bromatological (moisture, ash, fat, protein), physicochemical (pH, acidity, water retention capacity, emulsification capacity) and yield characteristics. In addition, a bifactorial AXB arrangement was applied, taking into account four treatments with three replicates, obtaining twelve experimental units. Thus, by means of the acid hydrolysis method, the bromatological characteristics, regardless of the dehydration temperature, allowed obtaining the best averages of protein, moisture and ash, while alkaline hydrolysis in combination with a temperature of 65°C allowed obtaining a higher percentage of fat. On the other hand, physicochemical analyses revealed that acid hydrolysis in combination with a temperature of 65°C yielded the best averages of pH, titratable acidity and emulsification capacity, while alkaline hydrolysis in combination with a temperature of 60°C yielded the best averages of water retention capacity. Finally, it was determined that the most efficient extraction method for obtaining collagen from chicken feet was alkaline hydrolysis at a dehydration temperature of 65°C, positioning T4 (alkaline hydrolysis + 65°C) with the highest collagen yield.